1967
DOI: 10.2307/1366200
|View full text |Cite
|
Sign up to set email alerts
|

Adipose Tissue Composition and Cell Size in Fall Migratory Thrushes (Turdidae)

Abstract: Fat deposition is one of the most important and constant physiological events associated with migration in birds (see reviews by King and Farner, 1956 and 1965; Farner, 1960; and Odum, 1960a, 1960b, and 1965). Odum, Rogers, and Hicks (1964) have advanced the hypothesis that before and during migration periods lipid deposition and depletion in adipose tissues occur without appreciable changes in the weight of water and other nonfat components in the body as a whole, in possible contrast to man, where changes in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

1967
1967
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(14 citation statements)
references
References 13 publications
1
13
0
Order By: Relevance
“…The adipocyte size at this time is similar to that in the adult goose (Clara, 1929), thrush (Hicks, 1967), rat (Goldrick, 1967) and man (Bjorntorp and Martinsson, 1966) and is therefore probably close to the size finally reached in the fully adult bird.…”
Section: Tissue Inguinal Adipose Tissuesupporting
confidence: 72%
“…The adipocyte size at this time is similar to that in the adult goose (Clara, 1929), thrush (Hicks, 1967), rat (Goldrick, 1967) and man (Bjorntorp and Martinsson, 1966) and is therefore probably close to the size finally reached in the fully adult bird.…”
Section: Tissue Inguinal Adipose Tissuesupporting
confidence: 72%
“…Johnston observed that migratory species tend to have more unsaturated fatty acids in adipose stores than non-migratory birds (Johnston, 1973), although Blem found no trend in saturation for migratory and non-migratory birds (Blem, 1976;Blem, 1980). Additionally, some researchers have noted a change in fatty acid composition leading up to migration, although this observation has not been consistent Hicks, 1967;McGreal and Farner, 1956) and does not seem to be the direct result of selective metabolism . Many authors have noted that adipose fatty acid composition tends to reflect dietary composition, and changes in bird diets leading up to migration can alter adipose stores (Bower and Helms, 1968;Conway et al, 1994;Morton and Liebman, 1974;West and Meng, 1968).…”
Section: Importance Of Selective Mobilization To Migratory Birdsmentioning
confidence: 98%
“…Supporting this hypothesis, several studies have shown that migrants have a higher proportion of unsaturated FA than non-migrants, and further, that migrants increase the relative unsaturation of fat stores prior to migration (Johnston, 1973;Conway et al, 1994;Egeler and Williams, 2000). Nonetheless, this observation has been inconsistent, and other researchers have found no difference between migrants and non-migrants with regard to adipose tissue FA composition (Hicks, 1967;Blem, 1976;McWilliams et al, 2004). We sought to extend this previous work by examining the seasonal changes in adipose and muscle FA composition in white-throated sparrows.…”
Section: Introductionmentioning
confidence: 96%